IMPLEMENTATION OF THE READING CORNER THROUGH THE SCHOOL LITERATURE MOVEMENT IN INCREASING STUDENT'S READING INTEREST IN ELEMENTARY SCHOOL - Sastra Wijaya, MS Zulela, Edwita, Gusti Yarmi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This study aims to determine students' reading interest through literacy movements in schools that implement reading corners in the classroom. This research was carried out at the Irsyadul Ibad Islamic Elementary School in Pandeglang Banten Province. The subjects in the study were fourth-grade students, totaling 40 students. The research uses descriptive qualitative methods, observation, and interviews as data collection instruments. The results showed that there was an increase in students' interest in reading after the implementation of the reading corner in the literacy movement at school. Students feel happy and comfortable in carrying out reading learning activities at school. The reading corner also impacts increasing the intensity of students' reading time because, through the implementation of the reading corner, students are given 15 minutes to read each before starting learning. Support for the literacy movement in schools is needed from various parties, such as teachers, principals, parents, and the community. Schools are expected to provide support for the availability of facilities and infrastructure to support the implementation of reading corner activities so that the reading corner has attractive decorations, a varied collection of books, and other representative supporting facilities. One obstacle in implementing the reading corner is students' boredom with reading. This happens because the concentration and focus of elementary school students are still easily distracted by playing activities, so teacher assistance is needed in this activity. Teachers must be facilitators and motivators for students in reading activities. In implementing reading corner activities, teachers are advised to carry out three activity stages: habituation, development, and literacy-based learning. A good literacy program must be balanced, and schools that implement a balanced literacy program must realize that each student has different learning styles and needs.